Valorization of aquaculture side streams from sea bream and sea bass by enzymatic hydrolysis and fractionation: chemical and biological insights - Jenssen, Marte; Sone, Izumi; Grasso, Federica; Turrini, Federica; Tardanico, Francesca; Atanasio, Giulia De Negri; Paz, Diego Méndez; Sobrado, Rebeca Vázquez; Martínez, Mercedes Alonso; Boggia, Raffaella; Grasselli, Elena; Lian, Kjersti (Frontiers in Nutrition, 2025)
Increased valorization of aquaculture side streams is essential for reducing waste and enhancing resource efficiency. This study investigates the enzymatic hydrolysis and subsequent fractionation of pre-processed side streams from sea bream and sea bass aquaculture. Using Corolase® 8000, hydrolysates were produced and fractionated into crude, permeate, and retentate using membrane filtration (3 kDa molecular weight cut-off). The samples were comprehensively characterized for chemical composition, techno-functional properties, and biological activities. Briefly, the chemical characterization revealed that all samples had high protein content (>80%). As expected, the highest average molecular weight was measured for the retentate, followed by the crude and the permeate. The permeate distinguishes itself from the other samples with a lighter color profile in the color analysis. In the techno-functional characterization, the retentate showed the most promising properties, surpassing in emulsifying activity, foaming capacity, and oil binding capacity, suggesting its potential in food applications. The crude had the highest stability to maintain foam and emulsion over time. The bioactivity screening revealed some activity in the hepatoprotective assay (reduced fatty acid accumulation), the cellular antioxidant assay, and the angiotensin-converting enzyme (ACE) inhibitory assay. The samples did not exhibit anti-inflammatory activity or anti-osteoporotic capacity. The most pronounced results from the bioactivity studies were found in the wound healing assay, where the permeate had significantly increased wound closure at all tested concentrations (0.05, 0.025, and 0.015 mg/mL), suggesting its potential for wound healing applications. These findings highlight the potential of fractionated fish protein hydrolysates as functional ingredients in nutraceutical and food formulations, supporting circular economy strategies in aquaculture.